Detection of G8P[1] bovine-like rotavirus in argentinean oysters. - Frydman, Camila Ayelén; Miño, Samuel; Barbieri, Elena; Seiler, Erina Noé; Galeano, Solange; Matthijnssens, Jelle; Parreño, Viviana; Mozgovoj, Marina Valeria (14th International dsRNA Virus Symposium, 2022)
Foodborne viruses are a leading cause of enteric diseases worldwide. Viruses can be transmitted by consumption of contaminated bivalve shellfish that are usually eaten raw or slightly cooked. These filter-feeding organisms can concentrate pathogens present in water in their digestive glands. The aim of this study was to determine the presence of rotavirus in oysters (Crassotrea gigas) collected from the south coast of Buenos Aires and Golfo Nuevo, Argentina. A total of 209 oysters were processed according to ISO/TS 15216-2:2019 standard of quality. RVA detection was carried out by real time RT-qPCR targeting the NSP3. The virus was detected in 20% of the pooled samples. Only two detected viruses could be characterized. The genotype of RVA from a pool of oysters collected at Golfo Nuevo was G8P[1] while a second pool from Isla Gama was isolated in cell culture demonstrating virus viability as infective particles were detected by immunofluorescence. The genotype constellation of the isolated strain was G8-P[1]-I2-R2-C2-M2-A3-N2-T6-E2-H3, which has a bovine-like genome backbone. Interestingly, RVA detected strains do not cluster closely previously bovine-like RVA reported strains from Argentina. These findings evidence the presence of infective RVA in oysters that can lead to potential outbreaks. Surveillance programs should be considered to prevent foodborne illnesses linked to ingestion of contaminated shellfish. Moreover, oysters could be used to monitoring environment polluted with viruses that affect human health.
Keywords: Ciencias naturales::Ciencias biológicas::Virología